2021
DOI: 10.3390/pharmacy9010021
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Electronic Nicotine Delivery Systems (ENDS) Cessation Methods

Abstract: Currently, 7.6% of the U.S. young adults aged 18–24 years old use e-cigarettes. This study piloted three methods of Electronic Nicotine Delivery Systems (ENDS) cessation by measuring cessation rates, motivational techniques that contributed to cessation success, and participants’ changes after decreasing vape use. Participants were randomized into three study arms (nicotine replacement therapy (NRT) + behavioral support, vape-taper + behavioral support, self-guided) in a 1:1:1 ratio. All participants were invi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…There are few published studies of behavioral or pharmacologic approaches for adolescent vaping cessation ( 45 , 64 , 65 ). Because varenicline has been found to be consistently more effective than other pharmacotherapies for smoking cessation in adults and has demonstrated encouraging secondary abstinence outcomes in two adolescent smoking cessation randomized controlled trials ( 33 , 34 ), we will conduct a rigorous three-armed randomized controlled trial in nicotine dependent adolescents of biochemically validated vaping abstinence with varenicline, combined with brief, lay counselor delivered behavioral counseling and texting support ( 27 , 29 , 30 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are few published studies of behavioral or pharmacologic approaches for adolescent vaping cessation ( 45 , 64 , 65 ). Because varenicline has been found to be consistently more effective than other pharmacotherapies for smoking cessation in adults and has demonstrated encouraging secondary abstinence outcomes in two adolescent smoking cessation randomized controlled trials ( 33 , 34 ), we will conduct a rigorous three-armed randomized controlled trial in nicotine dependent adolescents of biochemically validated vaping abstinence with varenicline, combined with brief, lay counselor delivered behavioral counseling and texting support ( 27 , 29 , 30 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reported quit importance was highest in the third and final survey time point, which occurred in April 2020, after the e-cigarette or vaping use-associated lung injury (EVALI) outbreak that began in July 2019 and resolution of its cause (ie, black market tetrahydrocannabinol [THC] products contaminated with vitamin E acetate) in February 2020 (25). We did not measure exposure to EVALI information; however, we suspect that the increased media attention to the potential harms of e-cigarettes in late 2019 may have contributed to the increased quit importance in the survey data collected in January 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Empirically supported treatments of e-cigarette cessation are lacking. A pilot trial showed promise for nicotine replacement therapy, tapering use, and self-guided methods for e-cigarette cessation among young adults ( 26 ). A randomized clinical trial among more than 2,000 young adult e-cigarette users found better cessation rates in a text-messaging program (24.1%) than in an assessment-only control condition after 7 months (18.6%) ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study of three different methods of e-cigarette cessation in current e-cigarette users explored the effectiveness of NRT and behavioral support, vape-taper and behavioral support, and self-guided cessation methods. Researchers determined that all methods demonstrated some effectiveness for e-cigarette and nicotine cessation, and that those in the vape-taper and behavioral arm were more likely to have stopped vape and nicotine use at 6 months [41].…”
Section: Recommendations To Address Puff Bar Use As a Parent Or Pedia...mentioning
confidence: 99%